Trees and sidewalks: toward an infrastructure protection approach - Otero-Durán, Laura; Torres, Andrés (Frontiers in Sustainable Cities, 2024)
Introduction Nature-based solutions are increasingly recognized as vital components of urban resilience strategies, particularly within the framework of green infrastructure. This study aims to propose an approach that fosters symbiosis between green and gray infrastructure to address the challenges posed by climate change in urban environments. Methods We conducted a comprehensive review of guidelines and scientific literature to inform the selection of species and the design of root containers for urban tree planting. Additionally, we performed a multicriteria analysis and assessed water comfort to guide decision-making regarding species selection in specific city areas. Results The methodology was applied to a case study in Bogotá, yielding insights applicable to any city with basic knowledge of suitable species for planting in built public spaces. Crucial criteria for selecting local species for sidewalks were identified, including size, permeability, soil compaction characteristics, and climatic adaptability. A list of desirable species adapted to all humidity zones of the case study city was generated. Hydrological sizing methods proposed are contingent upon both the species to be planted and the geometry of the streets. Discussion The approach and findings presented in this study promote the development of trees and their ecosystem services while mitigating potential damage to surrounding infrastructure. Conclusion Implementing strategies that facilitate symbiosis between green and gray infrastructure contributes to urban resilience and aids in climate change adaptation efforts.